The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.4049/jimmunol.178.6.3390
|View full text |Cite
|
Sign up to set email alerts
|

Serpin-6 Expression Protects Embryonic Stem Cells from Lysis by Antigen-Specific CTL

Abstract: The immune response to embryonic stem (ES) cells is still poorly understood. In this study, we addressed the adaptive cellular immune response to undifferentiated and differentiated ES cells infected with lymphocytic choriomeningitis virus (LCMV), a vertically transmitted pathogen in mice and humans. In contrast to the prevailing view, we found that undifferentiated and differentiated murine ES cells express MHC class I molecules, although at low levels. When cocultured with LCMV-infected ES cells, syngeneic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
84
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(96 citation statements)
references
References 42 publications
8
84
1
3
Order By: Relevance
“…Together, the expression of MHC-I and -II antigens on stem cell-derived grafts theoretically will determine the immunological reaction after transplantation (6,29,30,32,33). Previous reports showed that MHC-I molecules were not detected in mouse ESCs (1,17) but were detectable in undifferentiated hESCs at low levels (16,18,19,21,26). However, the expression of MHC-I molecules is increased after differentiation of mouse ESCs (15,38) and hESCs (4,(19)(20)(21)38).…”
Section: Discussionmentioning
confidence: 99%
“…Together, the expression of MHC-I and -II antigens on stem cell-derived grafts theoretically will determine the immunological reaction after transplantation (6,29,30,32,33). Previous reports showed that MHC-I molecules were not detected in mouse ESCs (1,17) but were detectable in undifferentiated hESCs at low levels (16,18,19,21,26). However, the expression of MHC-I molecules is increased after differentiation of mouse ESCs (15,38) and hESCs (4,(19)(20)(21)38).…”
Section: Discussionmentioning
confidence: 99%
“…Serine protease inhibitor 6 (Spi6) is the mouse homolog of PI-9 in humans and is required to protect CTLs from GrBmediated death (21,22). PI-9 is expressed in the cytoplasm and nuclei of CTLs, immunoprivileged cells (23), and embryonic stem cells (24); PI-9 overexpression allows for the evasion of GrBmediated cytotoxicity (25,26). Endogenous GrB inhibitors have been characterized in both mice and humans.…”
mentioning
confidence: 99%
“…In addition, because of their early stage of development, ESCs are considered "immune privileged," i.e, unrecognizable by the recipient immune defenses (Magliocca et al, 2006;Ichiryu and Fairchild, 2013). Moreover, it has been reported that mESCs are resistant to antigen-specific cytotoxic T lymphocyte (CTL) due to the expression of serpin-6, an endogenous inhibitor of granzyme B (Abdullah et al, 2007). Dressel et al (2008) stated that the MPI-II cells they used were susceptible to granule exocytosis-mediated killing by rat NK cells and also by peptide-specific mouse CTL.…”
Section: Discussionmentioning
confidence: 99%